Phytosynthesis of cerium oxide nanoparticles and investigation of their photocatalytic potential for degradation of phenol under visible light - Ahmad, T. (Elsevier B.V., 2020)
Nowadays, synthesis of cerium oxide nanoparticles (CeO2-NPs) via employing plants as reducing and stabilizing agents has been widely dealt by research community owing to their eco-friendly, simple, cost effective and renewability features. In the same line of action, current study has first time reported the formation of Elaeis guineensis leaves mediated CeO2-NPs. The phytochemicals corresponding to OâH, CdbndO and NâH functional groups displayed their major contribution as reducing and stabilizing agents in the formation of CeO2-NPs, revealed through Fourier transform infrared spectroscopy (FTIR). The formation of uniform agglomerated cubic structured CeO2-NPs containing particle size range 13â16 nm was confirmed through observing FTIR peak at 560 cmâ1, FESEM and EDAX results. The XPS and XRD revealed the chemical oxidation states of Ce3d and formation of cubic structured cerium oxide particles containing crystal size 5.2 nm. An excellent photocatalytic degradation potential was exhibited by biofabricated CeO2-NPs through demonstrating 92.24% removal efficiency in 360 min irradiation time under visible light. The kinetic modelling of CeO2-NPs for photocatalytic degradation of phenol was found to be followed by Langmuir Hinshelwood (L-H) model. Moreover, a photocatalytic degradation mechanism was also predicted to explain the removal phenomenon of phenol by employing CeO2-NPs photocatalyst. The experimental results concluded that Elaeis guineensis leaves can be employed as an inexpensive and nonhazardous potential bioresource for the synthesis of other metal oxide nanoparticles, which may have their applications in medical and environmental field. Â© 2020 Elsevier B.V.